2020
DOI: 10.1080/21645515.2020.1826250
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to influenza vaccination among different populations in Shanghai

Abstract: Background: Seasonal influenza vaccination coverage remains low in most areas of China. Its influencing factors and barriers in various populations receiving influenza vaccinations need to be well understood to promote vaccination. Methods: A cross-sectional survey was conducted with residents in 48 communities. Vaccination status in the 2018–2019 influenza season and reasons for or against vaccination were surveyed. The potential factors influencing vaccination uptake were determined using bivariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 16 publications
6
48
1
Order By: Relevance
“…Perhaps these participants had a better understanding of COVID-19 and its vaccine than those with lower educational background. A previous study on influenza vaccination in Shanghai obtained the same result [16]. This result also showed the importance of publicity and education among participants with low education level.…”
Section: Discussionsupporting
confidence: 74%
“…Perhaps these participants had a better understanding of COVID-19 and its vaccine than those with lower educational background. A previous study on influenza vaccination in Shanghai obtained the same result [16]. This result also showed the importance of publicity and education among participants with low education level.…”
Section: Discussionsupporting
confidence: 74%
“…However, few countries were able to achieve this threshold (11). Overall, the vaccination coverage among people with chronic diseases is higher than that in the general population (12). A cross-sectional study from Greece found that the highest vaccination coverage in people with chronic diseases who presented at primary health care facility was detected among people with chronic kidney disease (55.6%) and pulmonary disorders (53.9%) (13).…”
Section: Immunization Against Seasonal Influenzamentioning
confidence: 99%
“…Influenza vaccination is currently considered the most economical and effective way to prevent this disease [ 3 ]. Despite the wide availability and clear vaccination guidelines of influenza vaccines, vaccine uptake remains low among children in most countries, including China [ 4 , 5 ]. A meta-analysis including 126 studies showed that influenza vaccine coverage is less than 30% among children in mainland China [ 6 ].…”
Section: Introductionmentioning
confidence: 99%